2019
DOI: 10.1177/1074248419865287
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Adherence to Low-Dose Aspirin Treatment Among the French Population

Abstract: Background: Previous studies have shown that adherence to low-dose aspirin (LDA) is suboptimal. However, these studies were based on an average measure of adherence during follow-up, ignoring its dynamic process over time. We described the trajectories of adherence to LDA treatment among the French population over 3 years of follow-up. Methods: We identified a cohort of 11 793 new LDA users, aged ≥50 years in 2010, by using the French national health-care database. Patients included had at least 3 years of his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…All 28 papers were published in the last 10 years (2010-2020). Most studies were conducted in the United States (n = 17, 60.7%), 10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] while the remaining were conducted in Europe (n = 7, 25%), [35][36][37][38][39][40][41] Taiwan (n = 1, 3.6%), 42 and Australia (n = 2, 7.14%). 43,44 Although a variety of medical conditions were explored in GBTM populations, the majority of studies focused on populations diagnosed with cardiovascular diseases (n = 19, 67.9%).…”
Section: ■■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 28 papers were published in the last 10 years (2010-2020). Most studies were conducted in the United States (n = 17, 60.7%), 10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] while the remaining were conducted in Europe (n = 7, 25%), [35][36][37][38][39][40][41] Taiwan (n = 1, 3.6%), 42 and Australia (n = 2, 7.14%). 43,44 Although a variety of medical conditions were explored in GBTM populations, the majority of studies focused on populations diagnosed with cardiovascular diseases (n = 19, 67.9%).…”
Section: ■■ Resultsmentioning
confidence: 99%
“…43,44 Although a variety of medical conditions were explored in GBTM populations, the majority of studies focused on populations diagnosed with cardiovascular diseases (n = 19, 67.9%). 10,18,20,[22][23][24]27,29,30,[32][33][34][35][36][37][38]41,43,45 Study duration ranged from 9 months to 6 years, 38,42 with most lasting 2 years or less (n = 22, 78.6%). Table 1 summarizes the studies included in this review by the population characteristics, type of treatment, study duration, adherence measure, country, sample size, number of trajectory groups identified, and overview of the conclusions.…”
Section: ■■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Group-based trajectory modelling (GBTM) is increasingly used to describe the dynamic and mutable nature of medication adherence behaviors. [11][12][13][14] It is a statistical method for modelling a variable of interest throughout time or age by identifying groups of individuals with similar pro les. [15] The method was initially developed by Nagin et al to characterize developmental trajectories of criminal activities [16] and became prevalent for studying developmental trajectories in criminology, social science, and psychology.…”
Section: Introductionmentioning
confidence: 99%